POSSIBILITIES OF CABBAGE PRODUCTION UNDER CLIMATIC CHANGES - Červenski, Janko; Adamović, Boris; Vlajić, Slobodan; Zec, Srđan; Vojnović, Đorđe (Journal of Agricultural Sciences (Belgrade), 2025)
Cabbage growth and development require temperatures between 15 and 18 ºC. However, for most of the growing season, cabbage is exposed to temperatures above 20 ºC. To obtain the highest possible prices on farmer’s markets, cabbage producers start with the earliest possible dates for cabbage planting (early or late autumn). Cabbage growth is “pushed forward” by more abundant irrigation, planting density, cultivation, and protection, to form a marketable (technologically mature) head in the shortest possible time and achieve the highest possible profit on the market. To improve the efficiency of water use and adapt cabbage to warmer and drier conditions, it is recommended to use modified production systems, with an emphasis on postponing the date of sowing or planting to mitigate the effect of temperature increase and drought during cabbage production. This paper aims to point out the effect of temperature and water stress and to provide solutions that can be practically applied to mitigate the negative impact of the aforementioned stresses on cabbage production. Priority should be given to the development of production systems that improve the efficiency of water use adapted to the conditions of hot and dry weather. Irrigation of cabbage should be organized as drip irrigation as a more rational system, with the possibility of comparative feeding and protection.
Keywords: temperature stress, water stress, cabbage, irrigation, mulching